Migraine and aura in the genesis of mystical visions and artistic creation: the case of Hildegard von Bingen - Ferreira, Ermelinda Maria Araújo (Headache Medicine, 2011)
This essay analyses the critical and clinical interpretations of certain perception disturbances present in the aura of migraines, as represented in artistic works, according to the speculations of some researchers, but mainly focusing on the conclusions of the neurologist, Oliver Sacks. With the aim of promoting an interchange between the fields of science and humanities, the essay discusses both the limits of the art of curing and curing through art, citing the opinions of several doctors and writers concerning this matter. For this debate, particular focus is centered on the importance of the sui generis work of the German nun, artist and mystic, author of two of the first medical compendiums of the history of mankind and migraine sufferer: Hildegard von Bingen.